Analysis of fatigue and damage in glass-fibre-reinforced polypropylene composite materials - Ferreira, J. A. M. (1999)
This paper concerns fatigue studies of polypropylene/glass-fibre thermoplastic composites produced from a bi-directional woven cloth of co-mingled E-glass fibres and polypropylene fibres with a fibre volume fraction Vf of 0.338. The effect of lay-up design and load conditions on fatigue performance were investigated. The S-N curves, the rise in the temperature of the specimens, and the loss of stiffness during the tests, are discussed. Fatigue tests were performed in controlled displacement mode and in an imposed stress range. Similar results were obtained for both load conditions. The loss of stiffness was used as a damage parameter and related to the rise of temperature. The results show that the damage parameter E present a nearly linear relationship with the rise in temperature. A small deviation was probably caused by the stress release observed in the first period of fatigue life. ©